2019
DOI: 10.4018/ijdet.2019070101
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation of the UTAUT Model for Understanding Students' Perceptions of Learning Management Systems

Abstract: The rapid growth of e-learning around the globe is inspiring various academic institutions to adopt it. Uptake is motivated by convincing benefits such as flexibility, accessibility and the management of course delivery. In fact, academic institutions place great emphasis on e-learning and are investing significantly in information technology infrastructures. However, in spite of this effort and investment, it seems that instructors and students do not always fully benefit from the learning technology and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
48
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 59 publications
13
48
2
1
Order By: Relevance
“…Our findings have shown that behaviour intention has had a significant positive effect on the actual use of virtual classrooms. This finding is consistent with most previous studies which produced similar results (Alshehri et al, 2019;Lewis et al, 2013;Šumak et al, 2010;Sultana, 2020;Vankatesh et al, 2003). The findings have implied that when teaching staff have an intention to use virtual classrooms for teaching, this intention will lead to the actual use of virtual classrooms.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings have shown that behaviour intention has had a significant positive effect on the actual use of virtual classrooms. This finding is consistent with most previous studies which produced similar results (Alshehri et al, 2019;Lewis et al, 2013;Šumak et al, 2010;Sultana, 2020;Vankatesh et al, 2003). The findings have implied that when teaching staff have an intention to use virtual classrooms for teaching, this intention will lead to the actual use of virtual classrooms.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 94%
“…Venkatesh et al (2003) anticipated that if the relationships of PE and EE with BI exist, then FC becomes insignificant in predicating the behaviour intention toward the use of technology. The findings of this study were also consistent with certain previous studies where they found insignificant influence of FC on BI (Alshehri et al, 2019;Sultana, 2020). A possible explanation for these findings is that nowadays teaching staff can deal with and access technology from anywhere, at any time, without a need for FC, and they pay more attention toward the performance (usefulness of technology) and effort expectancy (ease of use of technology).…”
Section: Results Of Hypothesis Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…Many studies have shown that PE is a significant determinant of behavioural intention (BI) to use an e-learning system (Alrawashdeh et al, 2012;Alshehri et al, 2019a;Bellaaj et al, 2015;Bouznif, 2018;Salloum & Shaalan, 2019;Usoro et al, 2013). Similarly, in the Saudi higher education context, the studies of Alshehri et al (2019a) and Bellaaj et al (2015) found that performance expectancy has a remarkably positive impact on the students' intention to use an LMS. Thus, these findings suggest that the students are driven to accept the e-learning system primarily on the basis of its usefulness.…”
Section: Performance Expectancy (Pe)mentioning
confidence: 99%
“…Furthermore, recent studies have examined the use of e-learning systems in a Saudi higher institution and found that more than half of university students only use LMS either rarely or occasionally (Binyamin et al, 2016(Binyamin et al, , 2017. Prior studies disclosed that there is a dearth of academic research on Saudi higher education to examine the effects of usability factors on students use of LMSs, so significant issues have not yet been examined (Al-Asmari & Khan, 2014;Al-Harbi, 2011a;Alshammari et al, 2016;Alshehri et al, 2019a;Salloum & Shaalan, 2019;Yamani, 2014). Issues associated with system technical support, self-efficacy and instructional design, perceived accessibility, perceived flexibility, and subjective norm have been examined in the acceptance and use of LMSs (Al-Harbi, 2011a;Alshammari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%